The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.17979/rotur.2015.9.1.1338
|View full text |Cite
|
Sign up to set email alerts
|

Nuevas tecnologías para el desarrollo de la industria turística en Guanajuato, México

Abstract: El presente trabajo, trabajo de tipo exploratorio, expone un diagnóstico sobre la utilización de las tecnologías de información y comunicación (TIC´S) en 175 empresas turísticas de la ciudad de Guanajuato. Dentro de los principales resultados se pudo encontrar que la gran mayoría de las empresas incluye al menos una TIC para el desarrollo de sus actividades diarias. Dentro de las tareas más recurrentes en las cuales se encuentran dichas tecnologías son: comercialización, administración y servicio al cliente. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The 2021 survey of entrepreneurs (described in materials and methods section) found that business marketing is mainly digitalized, which concurs with previous sector studies (Mejía, 2015). Sales strategies use on-line web pages, Google Maps and search engines, Trip Advisor, Facebook, Instagram, and WhatsApp, while hotels use on-line travel agents (refer to networks, clusters and technology in the introduction)…”
Section: Sensitivitysupporting
confidence: 81%
“…The 2021 survey of entrepreneurs (described in materials and methods section) found that business marketing is mainly digitalized, which concurs with previous sector studies (Mejía, 2015). Sales strategies use on-line web pages, Google Maps and search engines, Trip Advisor, Facebook, Instagram, and WhatsApp, while hotels use on-line travel agents (refer to networks, clusters and technology in the introduction)…”
Section: Sensitivitysupporting
confidence: 81%